Hubungan Efikasi Diri dan Dukungan Sosial Keluarga Dengan Kematangan Karir pada Mahasiswa Keperawatan STIKES Muhammadiyah Lhokseumawe - Rahmia Dewi; Lahmuddin Lubis; Azhar Azhar (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
The aim of this study was to determine and analyze the relationship self eficacy and family social support with career maturity. The approach of this study was conducted by using correlational quantitative method. A total of 130 active student were employed and were obtained by using simple random sampling technique. Three scales namely career maturity, self- efficacy, and family social support were distributed to collect data. The data obtained was anylzed with Regression Analysis Technique. The results of this study indicate (1) there is a significant positive relationship between self efficacy and social support with career maturity, where the coefficient  rx12y= 0.580 and p= 0,000 with contribution of  33,6 %, there is a significant positive relationship between self efficacy and career maturity, where the coefficient  rx1y= 0.573 and p= 0,000 with contribution of  32,8%, there is a significant positive relationship between  social support and  career maturity, where the coefficient  rx2y= 0.347 and p= 0,000 with contribution of  12,0 %, thus, all hypotheses were accepted.